1988
DOI: 10.1111/j.1365-2338.1988.tb00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Coniothyrium minitans, Gliocladium roseum, Trichoderma harzianum and T. viride from alginate pellets and interaction with water availability1

Abstract: Conidia, chlamydospores and mycelia of Coniothyrium minitans, Gliocladium roseum, Trichoderma harzianum and T. viride were obtained from liquid or solid culture and formulated within alginate pellets. Quantitative assessment of these pellets over a 12‐week period showed a decrease in the number of colony‐forming units (cfu) from about 107 to 103‐104 g‐1 air‐dried pellets. Qualitatively, growth was assessed by direct plating the alginate pellets on rich (potato dextrose agar, PDA) and poor (water agar, WA) subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…This has already been done for other isolates directly (Wells, Bell & Jaworski, 1972;Beagle-Ristaino & Papavizas, 1985), or after forming alginate pellets which are easy to handle (Fravel et al, 1985 ;Lewis & Papavizas, 1985), to enable proliferation of the fungi to occur in the soil volume as a whole. This latter rocedure may, however, have some drawbacks in that germination from alginate pellets may be slow, particularly under low water potential (Magan & Whipps, 1987). Similarly, incorportion on the seed coat or roots could protect the underground parts and maximize the chances of protection when pathogen propagules are encountered (Lutchmeah & Cooke, 1985;Lifschitz, Windham & Baker, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…This has already been done for other isolates directly (Wells, Bell & Jaworski, 1972;Beagle-Ristaino & Papavizas, 1985), or after forming alginate pellets which are easy to handle (Fravel et al, 1985 ;Lewis & Papavizas, 1985), to enable proliferation of the fungi to occur in the soil volume as a whole. This latter rocedure may, however, have some drawbacks in that germination from alginate pellets may be slow, particularly under low water potential (Magan & Whipps, 1987). Similarly, incorportion on the seed coat or roots could protect the underground parts and maximize the chances of protection when pathogen propagules are encountered (Lutchmeah & Cooke, 1985;Lifschitz, Windham & Baker, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Water potential has been shown to strongly affect the activities of Trichoderma , including mycelial growth (Magan & Whipps, ; Kredics et al , ; Hussain et al , ), spore germination (Magan, ; Hussain et al , ), enzymatic activity (Kredics et al , , ) and their saprophytic activity (Eastburn & Butler, ). Hyphal growth, spore production and germination and biological control activity of Trichoderma species are generally negatively impacted by low soil water potentials (Eastburn & Butler, ; Clarkson et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Hussain et al () reported that the germination rate of T. viride and Gliocladium virens ( Trichoderma virens ) was maximum at osmotic potentials of −0.12 to −1.1 MPa, with maximum growth seen over an osmotic potential range of −0.12 to 2.15 MPa. Decreasing osmotic potential (−0.25 to −2.8 MPa) resulted in a decrease in mycelial growth (radial growth) of both T. harzianum and T. viride (Magan & Whipps, ). Similarly, mycelial growth of a T. harzianum isolate was inhibited by decreasing osmotic potential, with the secretion of enzymes implicated to be involved in mycoparasitism inhibited at low osmotic potential (Kredics et al , ).…”
Section: Introductionmentioning
confidence: 99%